2013
DOI: 10.1007/s10265-013-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes of gibberellin oxidase genes in grapevines with or without gibberellin application during inflorescence development

Abstract: The concept that gibberellin (GA) application on seeded grapevines induces seedlessness has been known for decades in viticulture. GA was applied to inflorescence clusters of seeded diploid grapevine cultivar 'Tamnara' (Vitis spp.) at 14 days before full bloom (DBF). Morphological and molecular effects of GA application were examined on the induction of parthenocarpic fruit development. With GA application, ovaries were enlarged and pollen tube growth was completely inhibited. Vitis GA oxidase enzymes, key det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
3
12
0
1
Order By: Relevance
“…These results imply that VvIAA9 , VvARF7 , and VvARF8 function as negative regulators of fruit set initiation, whose down-regulation leads to fruit set initiation. With GA application, however, VvIAA9 and VvARF7 were down-regulated 2 days after the application, and their transcription levels remained low until full bloom or 2 DBF, respectively (Figure 2A–B), in which expression levels of GA biosynthesis genes were down-regulated by GA application at 14 DBF [37]. These results indicate that effects of GA application at pre-bloom were not limited on transcriptional changes of these genes at 1 or 2 days after the application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results imply that VvIAA9 , VvARF7 , and VvARF8 function as negative regulators of fruit set initiation, whose down-regulation leads to fruit set initiation. With GA application, however, VvIAA9 and VvARF7 were down-regulated 2 days after the application, and their transcription levels remained low until full bloom or 2 DBF, respectively (Figure 2A–B), in which expression levels of GA biosynthesis genes were down-regulated by GA application at 14 DBF [37]. These results indicate that effects of GA application at pre-bloom were not limited on transcriptional changes of these genes at 1 or 2 days after the application.…”
Section: Discussionmentioning
confidence: 99%
“…However, although GA-mediated parthenocarpy is a highly desirable trait for table grapes, how GA induces parthenocarpic fruit development remains unclear. GA application at the pre-bloom stage in grapevines inhibited pollen tube growth and disturbed the balance of GA metabolism at near full bloom [37]. In the present study, changes in the expression levels of the fruit set related genes, VvIAA9 , VvARF7 , VvARF8 , and VvDELLA in grapevines were monitored to determine whether GA application coordinates auxin signaling during parthenocarpic fruit development.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To elucidate the molecular sources of the varietal differences in bioactive GA quantities described above, the spatio-temporal transcript levels of the rate-limiting 2-oxoglutarate-dependent dioxygenases (2-ODDs) gene families of grapevine ( VvGA20ox, VvGA3ox, VvGA2ox ) (Giacomelli et al, 2013; Jung et al, 2014) were quantified by qRT-PCR ( Figures 8A–C and Supplementary Figure S5). For consistency, the nomenclature of genes used in this study is same as reported in our previous study (Giacomelli et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…o efeito desses reguladores, em uvas apirenas, está vinculado, principalmente, ao aumento da divisão e da expansão celular (JunG et al, 2014). o efeito da giberelina é variável em função da cultivarcopa e do porta-enxerto, concentração, modo e época de aplicação e das condições ambientais (teCChio et al, 2009 ).…”
Section: Introductionunclassified